ANTIBIOTIC SUSCEPTIBILITY PATTERN OF CARBAPENEM RESISTANT ENTEROBACTERIACEAE AMONG UROPATHOGENS ISOLATED IN A REFERRAL LABORATORY OF KARACHI - Naseem, Saima; Fatima, Ambreen; Fasih, Fatima; Iqbal, Sahar; Gohar, Hareem; Zeeshan, Fouzia (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the antibiotic susceptibility pattern of Carbapenem resistant Enterobacteriaceae among uropathogens isolated in a referral laboratory in Karachi. Methodology: It is a retrospective cross-sectional study, carried out at the Department of Microbiology of Dow Diagnostic Research and Reference Laboratory. All urine samples collected during the study period of 6 months from October 2020 to March 2021 were tested for culture and sensitivity patterns by the disc diffusion method. Data of urine culture and sensitivity test reports were taken from the medical record. and analyzed by using SPSS version 16. Results: Out of the total 10925 uropathogens isolated, 67% belonged to Enterobacteriaceae family. The most frequent isolate among them was Escherichia coli 84% followed by Klebsiella species at 10%. The overall frequency of Carbapenem resistance was 6%. The frequency of Carbapenem resistance was higher in Klebsiella species 27% than Escherichia coli 8%. Multi-drug resistance was observed in both Escherichia coli and Klebsiella species especially against Ampicillin, followed by Cefixime, Cefuroxime, Ceftriaxone, Cotrimoxazole and Ciprofloxacin. Conclusion: The study showed a significant rate of Carbapenem resistance among Enterobacteriaceae which emphasizes the need for formulating an antimicrobial policy with its strict implementation and regular surveillance to control the spread of Carbapenem resistant Enterobacteriaceae at the hospital and community level.